Collective Abyss: Social Identities of Silence, Void, and Resistance - Sofya Chibisguleva; Elena Kilina (The February Journal)
Societies and policies are based on many factors, one of which is the assigning of value to people, processes, states, and results. Said value is never nil and is never singular; its assessment bar is a projection that fluctuates between a decided interpretation and an abyss of meanings (complete plurality). Within this spectrum, various laws of men and the Universe are the easiest to evaluate and assign value to, while empty spaces, silences, and idleness are the hardest. Since they are undefined entities, they might as well turn into entireties. The latter pose maximum threat to the value of non-empty spaces—the pillar of governance and control. Consequently, the social and especially political machine invented a separate system of assigning value to voids and silences. The regulatory spectrum of this system yearns for punishment, for the prevention of the abyss—complete plurality of choice and a lack of control. Chaos. This system of punishment is especially ruthless towards the arts, activism, and independent communities. This visual essay analyzes the two nodes within the above-mentioned system of evaluating negative spaces: a void and an abyss. Thinking through the lens of different occurrences, the text proposes their definitions (values) at different points of the punishment timeline for the use of silent, idle, and resting activists and artists who found themselves under the scorching heat of looming gore.